2021
DOI: 10.1111/btp.12908
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersal effectiveness by oilbirds (Steatornis caripensis) in the Southern Andes of Colombia

Abstract: Dispersal refers to the movement of individuals from the place of origin to other sites where they may establish and reproduce. In plants, this process mainly occurs through seed dispersal, and three hypotheses have been advanced to explain its relevance: escape, colonization, and directed dispersal (Howe & Smallwood, 1982). The escape hypothesis states that below and near parental trees there is a higher chance of mortality due to attack by pathogens and predators, as well as intra-specific competition (Conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Viable palm seeds have also been reported inside stomachs or in the dung of ungulates (e.g. Beck, 2006; Bodmer & Ward, 2006; Barcelos et al ., 2013), carnivores (Kays, 1999; Campos et al ., 2012), birds (Pizo & Simão, 2001; Cárdenas, Echeverry‐Galvis & Stevenson, 2021), primates (Stevenson & Link, 2010; Chaves, Stoner & Arroyo‐Rodríguez, 2012), turtles (Liu, Platt & Borg, 2004; Caputo & Vogt, 2008) and fish (Sório, Damasceno‐Junior & Parolin, 2015; Barbosa & Montag, 2017). Our review shows that seeds of more than 30 palm species have been reported to benefit from gut treatment that involves seed defecation.…”
Section: Interaction Outcomes In Palm–frugivore Interactionsmentioning
confidence: 99%
“…Viable palm seeds have also been reported inside stomachs or in the dung of ungulates (e.g. Beck, 2006; Bodmer & Ward, 2006; Barcelos et al ., 2013), carnivores (Kays, 1999; Campos et al ., 2012), birds (Pizo & Simão, 2001; Cárdenas, Echeverry‐Galvis & Stevenson, 2021), primates (Stevenson & Link, 2010; Chaves, Stoner & Arroyo‐Rodríguez, 2012), turtles (Liu, Platt & Borg, 2004; Caputo & Vogt, 2008) and fish (Sório, Damasceno‐Junior & Parolin, 2015; Barbosa & Montag, 2017). Our review shows that seeds of more than 30 palm species have been reported to benefit from gut treatment that involves seed defecation.…”
Section: Interaction Outcomes In Palm–frugivore Interactionsmentioning
confidence: 99%
“…Seed dispersal effectiveness serves as an indicator of the mutualistic relationship between plants and animals and is utilized to assess the role of animals in plant regenera-tion [18,19]. Over the last 15 years, seed dispersal by frugivores has been widely studied in primates [10,20], frugivorous birds [21,22], tortoises [23], and ungulates [24]. At the same time, our knowledge of seed dispersal effectiveness by frugivores has also greatly increased.…”
Section: Introductionmentioning
confidence: 99%